Three foxg1 paralogues in lampreys and gnathostomes—brothers or cousins? - Ermakova, Galina V.; Kucheryavyy, Alexander V.; Mugue, Nikolay S.; Mischenko, Aleksandr V.; Zaraisky, Andrey G.; Bayramov, Andrey V. (Frontiers in Cell and Developmental Biology, 2024)
Foxg1 is a key regulator of the early development of the vertebrate forebrain and sensory organs. In this study, we describe for the first time three foxg1 paralogues in lamprey, representative of one of two basally diverged lineages of vertebrates—the agnathans. We also first describe three foxg1 genes in sterlet—representative of one of the evolutionarily ancient clades of gnathostomes. According to the analysis of local genomic synteny, three foxg1 genes of agnathans and gnathostomes have a common origin as a result of two rounds of genomic duplications in the early evolution of vertebrates. At the same time, it is difficult to reliably establish pairwise orthology between foxg1 genes of agnathans and gnathostomes based on the analysis of phylogeny and local genomic synteny, as well as our studies of the spatiotemporal expression of foxg1 genes in the river lamprey Lampetra fluviatilis and the sterlet Acipenser ruthenus. Thus, the appearance of three foxg1 paralogues in agnathans and gnathostomes could have occurred either as a result of two rounds of duplication of the vertebrate common ancestor genome (2R hypothesis) or as a result of the first common round followed by subsequent independent polyploidizations in two evolutionary lineages (1R hypothesis).